Effect of pyrolysis temperature on pore development of oil palm-shell activated carbons - Herawan, Safarudin Gazali; Ayob, Md Razali (2009)
Oil-palm shells were used to prepare activated carbons. The shells were first subjected to a pyrolysis process and the resulting chars were then treated under a physical activation process in the presence of carbon dioxide. The influences of the temperature pyrolysis parameters on the activated carbon were investigated in particular. All the chars were subjected to fixed activation conditions, i.e., CO 2 flow rate of 400 cm3/min and heating rate of 10 ◦C/min under a nitrogen flow rate of 150 cm3/min. Surface area and porosimetry were carried out to evaluate their pore characteristics. The specific pore surface area and the micropore volume of the activated carbon were used as the criteria for selecting the optimum pyrolysis parameters. The optimum conditions for pyrolysis were a temperature of 800 ◦C, and hold time of 1 h.